IL-6/IL-6R Signaling Blockade Alleviates Chronic Allograft Rejection by Modulating Germinal Center B Cells and Allograft Inflammation in Murine Cardiac Transplantation - Xia R; Shi X; Zhang H; Zeng W; Yang Z; Xu J; Wang J; Miao Y; Liao T (Journal of Inflammation Research)
Renfei Xia,1,* Xiaoyi Shi,2,* Hengcheng Zhang,3,* Wenli Zeng,1 Zhe Yang,4 Jian Xu,1 Jianning Wang,4 Yun Miao,1 Tao Liao1,4 1Department of Transplantation, Nanfang Hospital, Southern Medical University, Guangzhou, 510515, People’s Republic of China; 2Department of Organ Transplantation, The Affiliated Guangdong Second Provincial General Hospital of Jinan University, Guangzhou, 510317, People’s Republic of China; 3Department of Urology, The Second Affiliated Hospital of Nanjing Medical University, Nanjing, 210003 People’s Republic of China; 4Department of Urology, The First Affiliated Hospital of Shandong First Medical University, Jinan, 250014, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tao Liao, Email liaot@mail2.sysu.edu.cn Yun Miao, Email miaoyunecho@126.comIntroduction: The activation of B cells to produce donor-specific antibody (DSA) and the infiltration of T and macrophages in the allografts are important factors leading to chronic rejection (CR). Interleukin-6 (IL-6) is particularly important in immune responses, playing a crucial role in the activation of B, T, and macrophages. In this study, we investigate the preventive efficacy and underlying mechanism of IL-6/IL-6R signaling blockade.Methods: The CR model in mice was constructed using allogeneic cardiac transplantation with CTLA4-Ig injection. We used anti-IL-6R monoclonal antibody tocilizumab and IL-6 knockout mice to block IL-6/IL-6R signaling, observed its preventive effects on CR, and explored the mechanism from its effects on B cell activation, DSA production, and inflammatory cell infiltration in the allografts.Results: IL-6/IL-6R signaling ablation significantly prolonged allograft survival and alleviated key pathological features of CR, including interstitial fibrosis, C4d deposition, inflammatory cell infiltration, myocardial ischemic necrosis, and neointimal hyperplasia. Mechanistically, blocking IL-6/IL-6R signaling reduced serum DSA-IgG levels, suppressed B cell response and germinal center B formation, and decreased inflammatory cell infiltration in allografts. Moreover, IL-6 knockout demonstrated superior efficacy compared to tocilizumab, suggesting that complete IL-6 signaling ablation offers greater protection against CR. This study also provides the first comprehensive assessment of IL-6/IL-6R blockade on germinal center B cells and graft-infiltrating immune cells, highlighting its dual role in attenuating humoral and cellular immune responses.Discussion: IL-6/IL-6R signaling represents a pivotal therapeutic target for CR, and its blockade offers a promising strategy for improving long-term allograft outcomes.Keywords: IL-6, IL-6R, chronic rejection, tocilizumab, cardiac transplantation